Biological Evaluation of Black Chokeberry Extract Free and Embedded in Two Mesoporous Silica-Type Matrices - Valentina Buda; Ana-Maria Brezoiu; Daniela Berger; Ioana Zinuca Pavel; Delia Muntean; Daliana Minda; Cristina Adriana Dehelean; Codruta Soica; Zorita Diaconeasa; Roxana Folescu; Corina Danciu (MDPI AG, 2020)
Black chokeberry fruits possess a wide range of biological activities, among which the most important that are frequently mentioned in the literature are their antioxidant, anti-inflammatory, anti-proliferative, and antimicrobial properties. The present paper reports, for the first time, the encapsulation of the ethanolic extract of Aronia melanocarpa L. fruits into two mesoporous silica-type matrices (i.e., pristine MCM-41 and MCM-41 silica decorated with zinc oxide nanoparticles). The aim of this work was to evaluate the antiradicalic capacity, the antimicrobial potential, and the effects on the cell viability on a cancer cell line (i.e., A375 human melanoma cell line) versus normal cells (i.e., HaCaT human keratinocytes) of black chokeberry extract loaded on silica-type matrices in comparison to that of the extract alone. The ethanolic polyphenolic extract obtained by conventional extraction was characterized by high-performance liquid chromatography with a photodiode array detector (HPLC-PDA) and spectrophotometric methods. The extract was found to contain high amounts of polyphenols and flavonoids, as well as good radical scavenging activity. The extract-loaded materials were investigated by Fourier transform infrared spectroscopy, N2 adsorption-desorption isotherms, thermal analysis, and radical scavenger activity on solid samples. The black chokeberry extract, both free and loaded onto mesoporous silica-type matrices, exhibited a significant antioxidant capacity. Antibacterial activity was recorded only for Gram-positive bacteria, with a more potent antibacterial effect being observed for the extract loaded onto the ZnO-modified MCM-41 silica-type support than for the free extract, probably due to the synergistic effect of the ZnO nanoparticles that decorate the pore walls of silica. The cellular viability test (i.e., MTT assay) showed dose- and time-dependent activity regarding the melanoma cell line. The healthy cells were less affected than the cancer cells, with all tested samples showing good cytocompatibility at doses of up to 100 µg/mL. Improved in vitro antiproliferative and antimigratory (i.e., scratch assay) potential was demonstrated through the loading of black chokeberry extract into mesoporous silica-type matrices, and the screened samples exhibited low selectivity against the tested non-tumor cell line. Based on presented results, one can conclude that mesoporous silica-type matrices are good hosts for black chokeberry extract, increasing its antioxidant, antibacterial (on the screened strains), and in vitro antitumor (on the screened cell line) properties.